Hubungan Tingkat Kebisingan Lalu Lintas Terhadap Kegiatan Belajar Mengajar Di Sekolah (Studi Kasus SDN Buaran 01, Tangerang Selatan) - Rahma Dewi Ayu Cahyandari; Hernani Yulinawati; MM. Sintorini Moerdjoko (Journal of Environmental Engineering and Waste Management, 2019)
This study aims to analyze the noise level in the Buaran 01 Elementary School and compare it with the standard noise level, and analyze the relationship of traffic to the disturbance of the school community. Data were collected for 2 weeks at 8 sampling points in the elemtary school area and 1 sampling point on the roadside with a sound level meter. Measurement and data processing methods are in accordance with KepMenLH No.48 of 1996. The results showed the relationship between the number of vehicles and the types of vehicles that passed by is 76.3 dB (A) with the noise level at 01 Buaran Elementary School of 74.6 dB (A). The environment noise level in the elementary school has exceeded the 55 dB (A) from noise level standard for the education area. The correlation between noise level and vehicle equivalent are 4.19% to 54.73% which shows that the noise level can also be influenced by the number of vehicles that passed. As many as 59% of respondents feel disturbed by the noise that occurs. The control efforts that can be done include making barriers in the form of plants, using sound dampening in the room, using door closer to doors and windows, avoiding doors with curved motives, and installing weather stripping in each window so that noises do not enter the window.